2017
DOI: 10.1051/matecconf/20179402005
|View full text |Cite
|
Sign up to set email alerts
|

Researches on evaluation of smooth entrance in cutting using electrical current. A case study

Abstract: Abstract. At metal drilling, at the beginning of the process, the cutting tool in the chisel edge zone, frictions and plastically deforms the material, and then enters in cutting. If the drill is entered smoothly in cutting with a special device, its life is increased. The paper presents how the electrical current at cutting is used for the evaluation of smooth entrance in cutting in comparison with classical cutting. These are demonstrated for 41MoC11 steel drilled with a set of 30 tools having 8 mm diameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The authors demonstrated, in a previous research [9], at drilling process, a connection between the electrical current at cutting and the quality of the cutting edges, by microscopically examination of the drills edges and identifying causes of the high electrical current voltage, and led to the conclusion that the electrical current is sensible to any imperfection of the drill edge. Based on this research, the authors developed, in research [10], a methodology for drills acquisition, where two drill batches from two different suppliers were compared from qualitative and economical point of view.…”
Section: Introductionmentioning
confidence: 93%
“…The authors demonstrated, in a previous research [9], at drilling process, a connection between the electrical current at cutting and the quality of the cutting edges, by microscopically examination of the drills edges and identifying causes of the high electrical current voltage, and led to the conclusion that the electrical current is sensible to any imperfection of the drill edge. Based on this research, the authors developed, in research [10], a methodology for drills acquisition, where two drill batches from two different suppliers were compared from qualitative and economical point of view.…”
Section: Introductionmentioning
confidence: 93%
“…The previous researches developed by the authors demonstrate a connection between the electrical current at cutting and the quality of the cutting edges, by microscopically examination of the drills edges and identifying causes of the high electrical current voltage [1]. The conclusion was that the electrical current is sensible to any imperfection of the drill edge.…”
Section: Introductionmentioning
confidence: 96%
“…An approach of the outlined issue is presented in other researches [1], where it was used the electrical current at cutting to analyse the quality of drills. Previous researches [2][3][4][5][6][7][8][9][10][11] conducted to the fact that the state of a cutting edge can be appreciated by the value of cutting electrical current voltage, because the higher this value is, the higher the initial temperature is.…”
Section: Introductionmentioning
confidence: 99%
“…The paper [5] presents a way to increase the durability of the drill by entering it smoothly into the cutting and analyzing the effectiveness of the method using the electrical current obtained from drilling 41MoC11 steel (breaking strength -950 N/mm 2 ) with a speed steel drill. 30 drills with a diameter of Ø8 mm, made of high-speed steel, were acquired.…”
Section: Introductionmentioning
confidence: 99%
“…1. Installation for measuring the electrical current at drilling with smooth entrance in cutting [5] Processing was performed with vc = 14.07 m/min and f = 0.25 mm/rev [5]. At the same time, the axial force at the drilling required to adjust the smooth entrance device was calculated Fx = 2560 N [5].…”
Section: Introductionmentioning
confidence: 99%